Escrevivências sobre a advocacia quilombola : uma experiência na Assessoria Jurídica Popular da Coordenação Nacional de Articulação das Comunidades Negras Rurais Quilombolas - Souza, Naryanne Cristina Ramos (2023)
This Dissertation is the result of my Master's research, carried out between the years 2021 and 2023. The research had as its guiding question: how did I become a popular quilombola lawyer? It is a writ as a lawyer in the Popular Legal Advice of CONAQ (National Coordination of Articulation of Rural Black Quilombola Communities), which represents approximately the six thousand quilombola communities existing in Brazil. I seek to highlight, in the tensions verified in the field, elements that help to build paths for quilombola theories-practices of Law. Therefore, my objectives were to write about my experiences as a quilombola lawyer, as well as to identify the challenges I encountered in legal practice, which began since graduation in Law, and how these challenges affect the practice of quilombola law, through the titling of quilombola territories.